2018
DOI: 10.3390/w10111550
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Moisture Sources and Climatic Teleconnections in Northeastern and South-Central Iran’s Hydro-Climatology

Abstract: Iran faces climate disparities due to extreme topographic anomalies, the Caspian Sea and the Persian Gulf water bodies, influences from diverse air masses and moisture sources, and its considerable area. FLEXPART model has been utilized to determine the main marine and continental moisture sources for south-central (Shiraz box) and northeastern (Mashhad box) parts of Iran. The marine moisture sources directly influenced extreme drought and wet conditions in Shiraz and Mashhad boxes during the wet period, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Four air masses including maritime polar (mP), Mediterranean (MedT), continental polar (also called the Siberian high-pressure system, cP), and continental tropical (also known as Sudan, cT) normally influence Iran in the wet period (November to April). However, the maritime tropical (mT) air mass only influences Iran in the dry period (May to October) [25,26]. The cP air mass predominantly supplies moisture from the Caspian Sea, and to a lesser extent from the Black Sea.…”
Section: Iran Climatology and Weather Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four air masses including maritime polar (mP), Mediterranean (MedT), continental polar (also called the Siberian high-pressure system, cP), and continental tropical (also known as Sudan, cT) normally influence Iran in the wet period (November to April). However, the maritime tropical (mT) air mass only influences Iran in the dry period (May to October) [25,26]. The cP air mass predominantly supplies moisture from the Caspian Sea, and to a lesser extent from the Black Sea.…”
Section: Iran Climatology and Weather Conditionsmentioning
confidence: 99%
“…References [15][16][17][18][19][20][21][22][23][24] developed MWLs for Mashhad, Sirjan, Tehran, Zarivar and Marivan, Khersan, western Zagros, Shahrood, Lar National Park, northeast Iran, and North Khorasan Province, respectively. Each of these MWLs is applicable to the region for which it was developed and cannot be used in other parts of Iran because of differences in altitude, latitude, precipitation, and temperature [25,26]. Therefore, there is a need to develop regional Iran MWLs that can be applied to larger areas of the country.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the Arabian and Red Seas have an influential impact on heavy precipitation in Iran (Farajzadeh et al, 2007) and also on the river-flow in central-south and northeastern parts of Iran (Heydarizad et al, 2018). The spatial distribution of Iran's precipitation is largely governed by the geographical position of both the mid-tropospheric trough over the Middle East and the Arabian anticyclone (Raziei et al, 2012(Raziei et al, , 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, in the study region, besides the moisture of the Persian Gulf and the Red Sea, the role of the moisture fluxes from the Mediterranean Sea in Iran and Iraq was largely decreased. This is due to the fact that the Azores high pressure system is reinforced over Iran and Iraq and causes a stable atmospheric condition preventing the transfer of moisture fluxes to this region (Heydarizad, 2018;Heydarizad et al, 2018aHeydarizad et al, , 2018b. Due to the weakness of the Azores high pressure system in fall (October, November, and December), moisture fluxes were observed again from the Mediterranean Sea in October, while from November to December, moisture fluxes were also observed from the Red Sea and the Persian Gulf besides the Mediterranean Sea (Fig.…”
Section: Effects Of Moisture Sources and Local Parametersmentioning
confidence: 99%